Solar energy : application, economics, and public perception - Adaramola, Muyiwa (Apple Academic Press, 2015)
Due to climate change, the rise in energy demand, and issues of energy security, more countries are being forced to reexamine their energy policies and consider more renewable sources of energy. Solar power is expected to play a significant role in the changing face of energy economies, due in a large part to the recent technological advances in the field and the significant decrease in cost. This book describes these advances and examines the current state of solar power from a variety of angles. The various sections of the book cover the following topics: an overview of hybrid solar energy systems, solar energy and conservation, current solar energy technologies, the economics of solar power, and public perceptions of solar energy. This easily accessible reference volume offers a comprehensive guide to this rapidly expanding field. Edited by Muyiwa Adaramola, a researcher at the Norwegian University of Science and Technology whose research focuses both on wind and solar energy, Solar Energy: Application, Economics, and Public Perception is an authoritative and easy-to-use reference, ideal for both researchers in the field and students who wish to gain an overview of this important and wide-ranging topic.